From the desk of Editor in Chief - Rahman, Md Tahminur (Anwer Khan Modern Medical College Journal, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18846 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 54